2004
DOI: 10.1515/jpm.2004.126
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endothelin-1 and clinical manifestations of neonatal sepsis

Abstract: Plasma ET-1 levels in neonatal sepsis are related to the severity of clinical manifestations, especially oliguria, acidosis and systemic hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Hence, ET-1 might also be a good marker to detect sepsis especially in newborns with the same reliability than CRP or PCT in adults. Figueras-Aloy et al (2004) demonstrated that plasma ET-1 levels in neonatal sepsis are related to the severity of clinical manifestations, especially oliguria, acidosis, and systemic hypotension. Taken together, proET-1 levels in CAP patients at admission may be independent predictors of short-term mortality and the need for ICU admission, correlating strongly with the CURB-65 score.…”
Section: Et-1 and Its Precursor Peptide Proet-1mentioning
confidence: 99%
“…Hence, ET-1 might also be a good marker to detect sepsis especially in newborns with the same reliability than CRP or PCT in adults. Figueras-Aloy et al (2004) demonstrated that plasma ET-1 levels in neonatal sepsis are related to the severity of clinical manifestations, especially oliguria, acidosis, and systemic hypotension. Taken together, proET-1 levels in CAP patients at admission may be independent predictors of short-term mortality and the need for ICU admission, correlating strongly with the CURB-65 score.…”
Section: Et-1 and Its Precursor Peptide Proet-1mentioning
confidence: 99%
“…There is substantial evidence that ET-1 is elevated in neonates and infants with pulmonary hypertension and that it is a marker of sepsis severity [2,3]. In fact, studies in animals and humans demonstrate that ET-1 causes pulmonary hypertension, and high plasma levels of ET-1 have been demonstrated in various septic conditions and are associated with morbidity and mortality in septic patients [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The production of excessive amounts of cytokines in response to an endotoxin is known to stimulate the production of ET-1 from the endothelium (1). There is substantial evidence that ET-1 is elevated in neonates and infants with pulmonary hypertension and that it can serve as a marker of sepsis severity (2,3).…”
mentioning
confidence: 99%